Differential musculoskeletal outcome reporting in patients receiving bempedoic acid or atorvastatin: a disproportionality analysis using the EudraVigilance database - Gazzaniga, Gianluca; Romio, Antonio; Galuppi, Chiara; Gentile, Elena; Valentino, Filomena; De Toni, Luca; Foschiatti, Michela; Gringeri, Michele; D’Onghia, Stefano; Menichelli, Danilo; Pastori, Daniele; Scatigna, Marco; et al. (Frontiers in Pharmacology, 2026)
BackgroundElevated low-density lipoprotein cholesterol (LDL-C) is a major risk factor for atherosclerotic cardiovascular disease. Statins are the first choice LDL-C-lowering drugs, but often associated with musculoskeletal disorders (MSDs), limiting adherence. Bempedoic acid (BA) is a newer LDL-C-lowering prodrug acting upstream of statins with limited muscle tissue activation, offering an alternative to statin-intolerant patients. However, recent evidence suggests a higher-than-expected rate of muscle-related adverse drug reactions (ADRs). This study compares muscle-related ADRs for BA and atorvastatin (ATO) using the European spontaneous reporting system.MethodsADRs reports were extracted from the earliest available date to 30 June 2024 and categorized by patient demographics and ADR type. Disproportionality analysis via Reporting Odds Ratios (RORs) was performed to assess differences in muscle-related ADRs between BA and ATO.ResultsA total of 78,930 ADR reports, respectively 2,667 for BA-only, 76,137 for ATO-only and 126 for coadministration, were analysed. MSDs were the most frequently reported events, significantly higher in BA-only than ATO-only recipients (ROR 2.25, 95% CI 2.08–2.43). Musculoskeletal and muscle discomfort showed the highest odds of association with BA (6.97, 95% CI 4.46–10.91 and 6.37, 95% CI 4.58–8.85, respectively). Conversely, more severe conditions such as creatine phosphokinase increase (ROR 0.44, 95% CI 0.34–0.57) and rhabdomyolysis (ROR 0.05, 95% CI 0.02–0.10) were more frequently reported for ATO-only recipients. Overall, muscle-related ADRs reported for BA showed lower severity.ConclusionUsing a Registry-based approach, we found increased odds of muscle-related ADR reports in BA recipients compared to ATO, although characterized by more favourable clinical outcomes. It is suggested to pay increased attention to consider drug-related causes of muscle symptoms when BA is used, particularly when in combination with statins.